Vegetables, fruits and herbs in health promotion - Watson, Ronald R. (CRC Press LLC, 2011)
The use of dietary vegetables and medicinal herbs to improve health is a phenomenon that is taking society by storm. Herbal products are now a multi-billion dollar business. Even more important, this business is built upon extremely little research data. The FDA is pushing the industry-with Congress' help- to base their claims and products on scientific phenomena.